2014
DOI: 10.1002/2013jg002600
|View full text |Cite
|
Sign up to set email alerts
|

A coupled geochemical and biogeochemical approach to characterize the bioreactivity of dissolved organic matter from a headwater stream

Abstract: The bioreactivity or susceptibility of dissolved organic matter (DOM) to microbial degradation in streams and rivers is of critical importance to global change studies, but a comprehensive understanding of DOM bioreactivity has been elusive due, in part, to the stunningly diverse assemblages of organic molecules within DOM. We approach this problem by employing a range of techniques to characterize DOM as it flows through biofilm reactors: dissolved organic carbon (DOC) concentrations, excitation emission matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 84 publications
8
75
0
Order By: Relevance
“…These NOM inputs are fresher and more labile; owing to their short residence times in soil they are less likely to undergo chemical or microbiological processes. Similar effects were demonstrated by Sleighter et al (2014), higher DOM biolabile concentrations were observed to the season of leaf fall due to increasing fresh DOM content in the leached. Biodegradation models of NOM 310 in aquatic environments showed that the degradation times of lignin residues to low-molecular (Dolgonosov and Gubernatorova, 2010).…”
Section: Quantification Of Nom Labile and Recalcitrant In Freshwater supporting
confidence: 79%
See 1 more Smart Citation
“…These NOM inputs are fresher and more labile; owing to their short residence times in soil they are less likely to undergo chemical or microbiological processes. Similar effects were demonstrated by Sleighter et al (2014), higher DOM biolabile concentrations were observed to the season of leaf fall due to increasing fresh DOM content in the leached. Biodegradation models of NOM 310 in aquatic environments showed that the degradation times of lignin residues to low-molecular (Dolgonosov and Gubernatorova, 2010).…”
Section: Quantification Of Nom Labile and Recalcitrant In Freshwater supporting
confidence: 79%
“…Some authors have differentiated aquatic NOM by lability or recalcitrance (Leenheer;Croué, 2003;Filella, 2009;Lindell;Granéli;Tranvik, 1995;Miller et al, 1997;Sleighter et al, 2014;Uyguner-Demirel;Bekbolet, 2011). Labile organic matter (LOM) is defined as a fraction of NOM that is more biodegradable.…”
mentioning
confidence: 99%
“…However, a previous study found no difference in bacterial respiration between permafrost and modern DOM when degraded by aquatic bacteria in the dark, despite large differences in aromatic C content (Cory et al, 2013). Thus, aromatic C may control bacterial respiration in some waters, but the composition of the aromatics present may be as important as the abundance of aromatic C (Sleighter et al, 2014). For example, Mann et al (2014) proposed that increased phenolic aromatics within modern DOM inhibited aquatic bacterial respiration (Freeman et al, 2001), compared to ancient permafrost DOM containing less aromatic C. Alternatively, aromatic C content may not be a causal factor in bacterial respiration; that is, other facets of DOM composition may contribute to variability in bacterial activity, such as molecular weight or oxidation state (Meyer, 1994;Amon and Benner, 1996;Vallino et al, 1996;Sun et al, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…This exemplifies that the exact chemical composition might be a more universal predictor of decay patterns than the degree of allochthony. With the increasing number of studies using the ultrahigh resolution mass spectrometry to understand the molecular drivers of DOM reactivity in a variety of systems (Gonsior et al, 2013;Sleighter et al, 2014;D'Andrilli et al, 2015;Kellerman et al, 2015;Hawkes et al, 2016b;Riedel et al, 2016;Kamjunke et al, 2017) a better understanding of the intrinsic controls of aquatic DOM reactivity becomes increasingly possible to achieve.…”
Section: General Trends In Reactivity Among Major Compound Groupsmentioning
confidence: 99%